2015
DOI: 10.3892/ijmm.2015.2412
|View full text |Cite
|
Sign up to set email alerts
|

Uncarboxylated osteocalcin inhibits high glucose-induced ROS production and stimulates osteoblastic differentiation by preventing the activation of PI3K/Akt in MC3T3-E1 cells

Abstract: Uncarboxylated osteocalcin, an osteoblast-derived protein, plays an important role in the regulation of glucose metabolism. It has previously been demonstrated that high glucose levels inhibit osteoblast proliferation and differentiation. However, the mechanisms through which uncarboxylated osteocalcin regulates osteoblast proliferation and differentiation under high glucose conditions remain unclear. Thus, in the present study, we aimed to examine the effects of uncarboxylated osteocalcin on the proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…In addition, increasing evidence indicates that Gprc6a can respond to osteocalcin in the pancreas, muscle, and testis . Previous studies in our laboratory showed that unOc not only upregulates Gprc6a expression but also simulates differentiation of MC3T3‐E1 cells into mature osteoblasts under high‐glucose conditions . Furthermore, osteocalcin gene knockdown in human MSCs decreased mineral species maturation and the total hydroxyapatite content .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, increasing evidence indicates that Gprc6a can respond to osteocalcin in the pancreas, muscle, and testis . Previous studies in our laboratory showed that unOc not only upregulates Gprc6a expression but also simulates differentiation of MC3T3‐E1 cells into mature osteoblasts under high‐glucose conditions . Furthermore, osteocalcin gene knockdown in human MSCs decreased mineral species maturation and the total hydroxyapatite content .…”
Section: Introductionmentioning
confidence: 79%
“…The vector containing His‐unOc was transformed into Escherichia coli , and the expression and purification of the unOc protein were performed as previously described . In short, His‐unOc protein expressed in E coli was purified on a Ni Sepharose™ 6 Fast Flow column (GE, 17531801) according to the manufacturer's instructions . Coomassie blue staining results show that the purity of the His‐unOc obtained by purification was greater than 95%.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the osteocalcin-associated cell proliferation is associated with PI3K/Akt and ERK1/2 signaling pathways (38,39). Osteocalcin is an osteogenic marker (40) and activation of the ERK1/2 signaling pathway induces osteocalcin expression (39,40). Accordingly, in the present study, it was speculated that salidroside treatment induces the secretion of osteocalcin via the PI3K/Akt and ERK1/2 pathways.…”
Section: Discussionmentioning
confidence: 80%
“…A previous study reported that salidroside enhanced the expression of osteocalcin and reversed H 2 O 2 -induced bone loss in overiectomized rats (1). In addition, the osteocalcin-associated cell proliferation is associated with PI3K/Akt and ERK1/2 signaling pathways (38,39). Osteocalcin is an osteogenic marker (40) and activation of the ERK1/2 signaling pathway induces osteocalcin expression (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in bone and mineral metabolism were reported in some studies as a result of elevated blood sugar [43] which is accompanied with oxidative stress and partly contributing to the development of osteoporosis [44]. Supplementation with the vegetable formula, in OVXT group, showed hypoglycemic effect.…”
Section: Resultsmentioning
confidence: 99%